THE DEVELOPMENT OF IMMERSIVE LEARNING BASED ON NATURAL USER INTERFACE (NUI) ON TABLE TENNIS EXERCISE - Tito, Tito Parta Wibowo; Ibnu, Ibnu Sina (STKIP Muhammadiyah Kuningan, 2024)
Abstract ____________________________________________________________ This research is a learning media development research with the theory used is Immersive Learning based on Natural User Interface. Immersive Learning is expected to help students to practice table tennis without the limitations of space and time tools because Immersive Learning emphasizes learning that is virtual with the help of the Kinect camera from the Xbox 360 so that it is as if students can experience table tennis learning practices directly without the limitations of tools such as table bet net and save space. This research aims to give a new impression in the game of table tennis by giving a modern impression with the technology provided through Immersive Learning Based on Natural User Interface (NUI). In addition, to facilitate the assessment of sports subjects, especially table tennis material because in practice the assessment of the psychomotor domain. In practice in the field, teachers only measure the psychomotor abilities of students approximately during the learning process without making clear indicators so that the objectives of practicum activities according to basic competencies in the curriculum. Thus resulting in the usual subjectivity and unfavorable to improving the quality of learning. This study aims to help students know the level of objectivity in learning the basic movements of table tennis with the ADDIE development model. The research subjects used X grade students of Senior High School Number 1 South Bengkulu with 10 students. The development results that have been validated by media experts and material experts get a very valid category. While the results of the Immersive Learning application trial were determined by looking at the results of the individual trial with a score of 97.5% and the field test with a score of 95.5%. These results show that table tennis Immersive Learning is declared quite effective in improving psychomotor learning outcomes. Under the license CC BY-SA 4.0